2014
DOI: 10.1007/s13181-014-0419-y
|View full text |Cite
|
Sign up to set email alerts
|

Massive Atenolol, Lisinopril, and Chlorthalidone Overdose Treated with Endoscopic Decontamination, Hemodialysis, Impella Percutaneous Left Ventricular Assist Device, and ECMO

Abstract: Background Overdose of cardiovascular medications is increasingly associated with morbidity and mortality. We present a case of substantial atenolol, chlorthalidone, and lisinopril overdose treated by multiple modalities with an excellent outcome. Conclusion Aggressive medical intervention did not provide sufficient hemodynamic stability in this patient with refractory cardiogenic and distributive shock. Impella® percutaneous left ventricular assist device and extracorporeal membrane oxygenation provided suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Data for continuous kidney replacement therapy (CKRT) are sparse: in 3 cases of atenolol overdose, CKRT removed between 8 and 25% of total body burden adjusted for a 6-h period [ 120 , 123 , 128 ], with atenolol clearance ranging from 20 to 48 mL/min. In one sotalol overdose, CKRT clearance was estimated as 53 mL/min [ 122 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data for continuous kidney replacement therapy (CKRT) are sparse: in 3 cases of atenolol overdose, CKRT removed between 8 and 25% of total body burden adjusted for a 6-h period [ 120 , 123 , 128 ], with atenolol clearance ranging from 20 to 48 mL/min. In one sotalol overdose, CKRT clearance was estimated as 53 mL/min [ 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…For atenolol (n = 9), when hemodialysis was used, an increase in blood pressure was noted after the first treatment, with one exception [ 129 ]. Again, apparent improvement was slower with CKRT [ 120 , 127 , 128 ]. Dysrhythmias recurred in two patients, within two hours of ECTR cessation, requiring another session [ 13 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cardiac pacing may be effective in increasing the rate of myocardial contraction however, electrical capture is not always successful and adequate blood pressure may not be restored [5]. It is not known how nodal agent toxicity will behave in the setting of an LVAD, though a handful of case reports described successful resuscitation of patients using percutaneous left ventricular assist (Impella) heart pump devices [6][7][8]. This is an interesting area of future research as one study has shown increased rates of suicide in patients with LVADs [9].…”
Section: Discussionmentioning
confidence: 99%